2013
DOI: 10.2139/ssrn.2262018
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Fire Sales in the Tri-Party Repo Market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Martin, Skeie and von Thadden (2011) provided a model for a run in repo markets that takes into account the empirical facts of the Bear Stearns and Lehman crises. They showed that runs on repos occurred both in the bilateral repo market (characterized by a sharp increase in haircuts) and in the tri-party repo market (Begalle et al (2013). showed that in this market the level of margins and the amount of funding remained stable for most borrowers during the crisis.…”
Section: Executive Summarymentioning
confidence: 99%
“…Martin, Skeie and von Thadden (2011) provided a model for a run in repo markets that takes into account the empirical facts of the Bear Stearns and Lehman crises. They showed that runs on repos occurred both in the bilateral repo market (characterized by a sharp increase in haircuts) and in the tri-party repo market (Begalle et al (2013). showed that in this market the level of margins and the amount of funding remained stable for most borrowers during the crisis.…”
Section: Executive Summarymentioning
confidence: 99%
“…Asset fire sales have the potential to amplify and transmit systemic risk through two possible channels: (i) fire sales of assets when a dealer faces default and sells securities in its inventory preemptively to raise liquidity, and (ii) broader fire sales of assets by repo investors, who liquidate securities held as collateral after a dealer default has occurred (see Begalle et al, 2013). The first type of fire sale is being addressed, albeit partially, through prudential regulations that encourage individual firms to reduce reliance on short-term repo funding.…”
Section: Risk Of Fire Salesmentioning
confidence: 99%
“…This is but one example. There is also a literature on fire sales in New York financial markets, e.g Begalle et al (2013); Duarte and Eisenbach (2014); Gorton and Metrick (2012); Krishnamurthy et al (2012).…”
Section: Introductionmentioning
confidence: 99%